The effects of goal publicity and incentives on self-set performance goals - Chen, Clara Xiaoling (2021)
Many companies encourage employees to set their own performance goals and do not attach formal incentives to the achievement of these goals. In this environment, some organizations make employees' self-set performance goals public while other organizations do not. We predict that, due to strategic concerns induced by goal publicity and competition, making goals public will be more likely to lead employees to lowball their goals when they work under tournament incentives than under piece-rate incentives. Consistent with this prediction, our experimental results reveal that making self-set performance goals public decreases goal level under tournament incentives, but has no significant effect on goal level under piece-rate incentives. Results of our study suggest that the practice of making self-set goals public is potentially more compatible with organizations with a collaborative culture than those with a competitive culture.